Antibacterial efficacy of silver nanoparticles against multi-drug resistant clinical isolates from post-surgical wound infections. (June 2017) - Kasithevar, Muthupandi; Periakaruppan, Prakash; Muthupandian, Saravanan; Mohan, Mahalakshmi
Abstract: In order to investigate new effective and inexpensive nano-therapeutic approach for P. aeruginosa, staphylococcus aureus and coagulase negative staphylococci (CoNS), the present study reports an eco-friendly process for rapid synthesis of silver nanoparticles (Ag-NPs) using aqueous leaf extract of Corchorus Capsularis (CRCP). Formation of stable Ag-NPs at different time intervals gives mostly spherical particles with diameters ranging from 5 to 45 nm. The resulting Ag-NPs were characterized using Ultraviolet visible (UV–Vis) spectroscopy, Fourier Transform Infrared (FT-IR) spectroscopy, X-Ray Diffraction (XRD) analysis, Transmission Electron Microscopy (TEM) and Energy Dispersive X-ray analysis (EDX). XRD study shows that the particles are crystalline in nature with face centered cubic geometry. TEM studies show the formation of Ag-NPs with average size of 20.52 nm. The antimicrobial activity of the synthesized Ag-NPs was investigated against multi drug resistant (MDR) P. aeruginosa, Staphylococcus aureus and CoNS isolates from post-surgical wound infections. The present study suggests that Ag-NPs synthesized from aqueous leaf extract of CRCP shows significant antibacterial potential against MDR isolates from post-surgical wound infections. Graphical abstract: Highlights: Ag-NPs with antimicrobial efficacy against multi drug resistant isolates from post-surgical wound infections. Ag-NPs possess minimal cytotoxicity towards mouse embryo fibroblast cell line. Ag-NPs can act as a biocompatible nanomaterial for producing wound healing bandages.